The Transcriptional Differences of Avian CD4+CD8+ Double-Positive T Cells and CD8+ T Cells From Peripheral Blood of ALV-J Infected Chickens Revealed by Smart-Seq2 - Dai, Manman; Zhao, Li; Li, Ziwei; Li, Xiaobo; You, Bowen; Zhu, Sufang; Liao, Ming (Frontiers in Cellular and Infection Microbiology, 2021)
It is well known that chicken CD8+ T cell response is vital to clearing viral infections. However, the differences between T cell subsets expressing CD8 receptors in chicken peripheral blood mononuclear cells (PBMCs) have not been compared. Herein, we used Smart-Seq2 scRNA-seq technology to characterize the difference of chicken CD8high+, CD8high αα+, CD8high αβ+, CD8medium+, and CD4+CD8low+ T cell subsets from PBMCs of avian leukosis virus subgroup J (ALV-J)-infected chickens. Weighted gene co-expression network analysis (WGCNA) and Trend analysis revealed that genes enriched in the “Cytokine–cytokine receptor interaction” pathway were most highly expressed in the CD8high αα+ T cell population, especially T cell activation or response-related genes including CD40LG, IL2RA, IL2RB, IL17A, IL1R1, TNFRSF25, and TNFRSF11, suggesting that CD8high αα+ T cells rather than other CD8 subpopulations were more responsive to ALV-J infections. On the other hand, genes involved in the “FoxO signaling pathway” and “TGF-beta signaling pathway” were most highly expressed in the CD4+CD8low+ (CD8low+) T cell population and the function of CD4+CD8low+ T cells may play roles in negatively regulating the functions of T cells based on the high expression of CCND1, ROCK1, FOXO1, FOXO3, TNFRSF18, and TNFRSF21. The selected gene expressions in CD8+ T cells and CD4+CD8low+ double-positive T cells confirmed by qRT-PCR matched the Smart-Seq2 data, indicating the reliability of the smart-seq results. The high expressions of Granzyme K, Granzyme A, and CCL5 indicated the positive response of CD8+ T cells. Conversely, CD4+CD8+ T cells may have the suppressor activity based on the low expression of activation molecules but high expression of T cell activity suppressor genes. These findings verified the heterogeneity and transcriptional differences of T cells expressing CD8 receptors in chicken PBMCs.